2016
DOI: 10.1080/13825585.2016.1158235
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of unitization in mitigating age-related relational learning impairments depends on existing cognitive status

Abstract: Binding relations among items in the transverse patterning (TP) task is dependent on the integrity of the hippocampus and its extended network. Older adults have impaired TP learning, corresponding to age-related reductions in hippocampal volumes. Unitization is a training strategy that can mitigate TP impairments in amnesia by reducing reliance on hippocampal-dependent relational binding and increasing reliance on fused representations. Here we examined whether healthy older adults and those showing early sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
33
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 53 publications
5
33
0
Order By: Relevance
“…Given the well‐documented age‐related decreases in associative memory performance (Naveh‐Benjamin, ; Naveh‐Benjamin, Brav, & Levy, ; Naveh‐Benjamin, Guez, Kilb, & Reedy, ; Old & Naveh‐Benjamin, ) along with an increased reliance on familiarity‐based responding among older adults (Anderson et al, ; Bartlett & Fulton, ; Yonelinas, ), several studies have explored unitization as a method to improve associative memory performance in older adults (Ahmad et al, ; Bastin et al, ; D'Angelo et al, ; D'Angelo et al, ; Zheng et al, ). Across these studies, unitization consistently benefited older adults and reduced, but did not necessarily remove the difference in associative memory performance between age groups (Memel & Ryan, ; Zheng et al, ; Ahmad et al, ; Bastin et al, ; Bader et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the well‐documented age‐related decreases in associative memory performance (Naveh‐Benjamin, ; Naveh‐Benjamin, Brav, & Levy, ; Naveh‐Benjamin, Guez, Kilb, & Reedy, ; Old & Naveh‐Benjamin, ) along with an increased reliance on familiarity‐based responding among older adults (Anderson et al, ; Bartlett & Fulton, ; Yonelinas, ), several studies have explored unitization as a method to improve associative memory performance in older adults (Ahmad et al, ; Bastin et al, ; D'Angelo et al, ; D'Angelo et al, ; Zheng et al, ). Across these studies, unitization consistently benefited older adults and reduced, but did not necessarily remove the difference in associative memory performance between age groups (Memel & Ryan, ; Zheng et al, ; Ahmad et al, ; Bastin et al, ; Bader et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, an arrow turns from facing upward to facing the circle and then compresses the circle. Both healthy older adults (D'Angelo et al, , ) and individuals with MTL amnesia (D.A. in Ryan et al, ; N.C. in D'Angelo et al, ) exhibited better learning of arbitrary relations when provided with a unitizing animation, suggesting that unitized learning does not rely on hippocampus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Critically, the investigators did not indicate any age‐related differences in transverse patterning performance, perhaps because all participants were explicitly trained prior to the task, whereas the Driscoll et al () study required incidental trial and error for skill acquisition. Recent reports have also confirmed that semantic information (Ostreicher et al, ) and unitization (D'Angelo et al, ) improve impaired transverse patterning performance in cognitively normal older adults; unitization does not aid performance in older adults who do not earn passing scores (n ≥ 26/30) on the Montreal Cognitive Assessment (MoCA), however (D'Angelo et al, in press). Although these studies yielded important findings, researchers have not explored transverse patterning performance in a pattern separation context by dichotomizing cognitively normal older adults into impaired and unimpaired subgroups based on the HVLT‐R.…”
Section: Introductionmentioning
confidence: 89%